Inhibition of autophagy exerts anti-colon cancer effects via apoptosis induced by p53 activation and ER stress. Issue 1 (December 2015) - Sakitani, Kosuke; Hirata, Yoshihiro; Hikiba, Yohko; Hayakawa, Yoku; Ihara, Sozaburo; Suzuki, Hirobumi; Suzuki, Nobumi; Serizawa, Takako; Kinoshita, Hiroto; Sakamoto, Kei; Nakagawa, Hayato; Tateishi, Keisuke; et al.
Abstract Background Although some molecularly targeted drugs for colorectal cancer are used clinically and contribute to a better prognosis, the current median survival of advanced colorectal cancer patients is not sufficient. Autophagy, a basic cell survival mechanism mediated by recycling of cellular amino acids, plays an important role in cancer. Recently, autophagy has been highlighted as a promising new molecular target. The unfolded protein response (UPR) reportedly act in complementary fashion with autophagy in intestinal homeostasis. However, the roles of UPR in colon cancer under autophagic inhibition remain to be elucidated. We aim to clarify the inhibitory effect of autophagy on colon cancer. Methods We crossedK19 CreERT andAtg5 flox/flox mice to generateAtg5 flox/flox /K19 CreERT mice.Atg5 flox/flox /K19 CreERT mice were first treated with azoxymethane/dextran sodium sulfate and then injected with tamoxifen to inhibit autophagy in CK19-positive epithelial cells. To examine the anti-cancer mechanisms of autophagic inhibition, we used colon cancer cell lines harboring different p53 gene statuses, as well as small interfering RNAs (siRNAs) targeting Atg5 and immunoglobulin heavy-chain binding protein (BiP), a chaperone to aid folding of unfolded proteins. Results Colon tumors inAtg5 flox/flox /K19 CreERT mice showed loss of autophagic activity and decreased tumor size (the total tumor diameter was 28.1 mm in the control and 20.7 mm inAtg5 flox/flox /K19 CreERT mice, p  = 0.036). We found that p53 and UPR/endoplasmic reticulum (ER) stress-related proteins, such as cleaved caspase 3, and CAAT/enhancer-binding protein homologous protein, are up-regulated in colon tumors ofAtg5 flox/flox /K19 CreERT mice. Although Atg5 and BiP silencing, respectively, increased apoptosis in p53 wild type cells, Atg5 silencing alone did not show the same effect on apoptosis in p53 mutant cells. However, co-transfection of Atg5 and BiP siRNAs led to increased apoptosis in p53 mutant cells. Conclusions Blocking autophagy has potential in the treatment of colon cancer by inducing apoptosis via p53 and ER stress, and suppressing the UPR pathway is a valid strategy to overcome resistance to autophagic inhibition.